Implementasi Kebijakan PEKPPP (Pemantauan dan Evaluasi Kinerja Penyelenggaraan Pelayanan Publik) di Puskesmas Tanah Kali Kedinding - Rafani, Syafela Ristia; Lubis, Lunariana (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2024)
Service is one form of parameter as an effort to satisfy the needs of both organizations and individuals, because basically the service provided by organizations and individuals is a picture that reflects the quality of the service itself. Public services themselves will continue to experience changes as times change by using current technology. One form is a program from the Ministry of State Apparatus Empowerment and Bureaucratic Reform, namely the PEKPPP program, public services also include the health sector. One of the services provided by the government in the health sector is community health centers held in each region. Puskesmas is one of the Public Service Units, which means it participates in the PEKPPP program held by the Ministry of State Apparatus Empowerment and Bureaucratic Reform. The location of this research is at the Tanah Kali Kedinding Community Health Center. The theory used in this research uses the policy implementation theory by George C. Edward III that policy implementation is influenced by several variables, Communication, Resources, Disposition, and Bureaucratic Structure. The implementation of the PEKPPP program at the Tanah Kali Kedinding Community Health Center is going quite well, although it is experiencing obstacles in the form of data supporting documents that are not well organized. The 2 employees who are responsible for implementing the PEKPPP program at the Tanah Kali Kedinding Community Health Center seem to have mastered the PEKPPP program quite well, seen from their availability in providing the necessary supporting data despite difficulties due to having multifunctional tasks and the lack of clarity in the existence of a special team for the PEKPPP program at the Tanah Kali Kedinding Community Health Center